Developing Emissions Quantification Protocols for Carbon Pricing : A Guide to Options and Choices for Policy Makers - Partnership for Market Readiness (World Bank, Washington, DC, 2020)
Carbon pricing is an important instrument in addressing climate change. However, a well-functioning carbon pricing instrument needs a robust framework to quantify GHG emissions (including removals) underpinned by high quality data. This data can help policy makers set the level of a carbon tax (CT) and help regulators track how many emissions allowances companies need to surrender under an Emissions Trading System (ETS). A robust framework will facilitate implementation and enforcement of the rules and increase compliance levels. This report builds on the PMR Guide for Designing Mandatory Greenhouse Gas Reporting Programs (PMR MRV Guide), which provides a broader overview of establishing an MRV system. This report focuses on the technical detail of quantification protocols, that is, how in practice emissions data can be monitored and quantified for reporting. This report is intended for policy makers and government officials responsible for setting up and implementing emissions quantification protocols as part of the emissions monitoring, reporting, and verification (MRV) systems that support carbon taxes and emissions trading systems.